FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI SAWI DI DESA MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Shorea Khaswarina; Suardi Tarumun; Etik Purnami (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The most people in Indonesia depend of the live at agriculture sector. The vegetables are one of agriculture comodity can to give big contribute to economy if attemted optimally. The efforts of improvement the vegetable production influenced by factors  are  environment  (climate,  soil,  etc),  production  facility  (seed,  fertilizer, pesticide), capital and human resources. The research aim are to analyze influence  of production  factors  to  vegetable  produce  and  analyze  of  allocation  efficiency  of production  factors  using  to  mustard  farm.  This  research  was  conducted  in  the Maharatu Village Marpoyan Damai Subdistrict using the purposive sampling method with 40 mustard farmers. The results showed that production of mustard influenced by the seed, manure, urea, NPK, pesticide and labor with belief level 99 %. Score of MPP for  all  production  variable  showed  that  must  add  volume  of  production  factors  to increase mustard production.  NPM/px value for seed and urea manure is big than 1 that  mean the  farmers  can  be  add  volume  of  production  factors.  For  NPK  manure, pesticide and labor must not be increasing because value of NPM/px is small than 1 to reach efficient condition economically and get optimally benefit.